2020
DOI: 10.4067/s0717-95022020000400975
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation of the Best Site Based on the Distribution Pattern of Extramuscular and Intramusular Nerves for Gluteal Muscle Injection

Abstract: To reveal the extra-and intramuscular nerve distribution patterns of the gluteus maximus, medius, and minimus, and to provide guidance for gluteal muscle injection in order to avoid nerve injury. Ten adult and 10 child cadavers were used. The superior and inferior gluteal nerves innervating the gluteus maximus, medius, and minimus were dissected, exposed, and sutured in-situ on the muscle. The three gluteal muscles were removed, and the distribution patterns of the intramuscular nerves were revealed by modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Only one previous paper confirmed the intramuscular neural distribution pattern in the Gmax. In that study, Junxi Wu et al also visualized the intramuscular neural distribution of Gmax through Sihler's staining, but they based their analysis on the surface structure of the ilium crest and gluteal sulcus [30], so they could not confirm the distribution pattern in the three segments of the Gmax. We first classified the three segments and then identified the nerve distribution pattern within each one.…”
Section: Discussionmentioning
confidence: 98%
“…Only one previous paper confirmed the intramuscular neural distribution pattern in the Gmax. In that study, Junxi Wu et al also visualized the intramuscular neural distribution of Gmax through Sihler's staining, but they based their analysis on the surface structure of the ilium crest and gluteal sulcus [30], so they could not confirm the distribution pattern in the three segments of the Gmax. We first classified the three segments and then identified the nerve distribution pattern within each one.…”
Section: Discussionmentioning
confidence: 98%
“…The safety of the ventrogluteal site has also generated doubts. Some studies present an area that is not exempt from risks (Obach et al, 1983; Wu et al, 2020), or other types of adverse effects (Müller‐Vahl, 1985; Wu et al, 2020). This type of injuries is underdocumented, in relation to adverse effects in DS.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent medical literature has provide evidence of the safety and efficacy of this site, highlighting its distance from the sciatic nerve (Yalcin et al, 2015), relatively low number of veins present (except some branches of superior gluteal artery or vein; Nakajima et al, 2020) and the reduced thickness of the subcutaneous tissue in comparison with the dorsogluteal site (Arslan & Özden, 2018; Elgellaie et al, 2018; Larkin et al, 2018; Nisbet, 2006). However, some studies present ventrogluteal site as an area that is not exempt from risks (Müller‐Vahl, 1985; Obach et al, 1983; Wu et al, 2020). The safety of the ventrogluteal site has also generated doubts.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies exist describing the importance of injection sites and needle length in pigs, i.e., [ 11 , 12 ]. Human and animal research [ 16 , 17 , 18 , 19 , 26 , 27 ] have shown that the optimum injection depth results in less pain and being transferred to animals might result in higher animal welfare. This is of great importance, even if irritating inoculums or vaccines are used, which can result in large-scale tissue alterations [ 1 , 2 , 5 , 6 , 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%